2018
DOI: 10.1051/shsconf/20184200046
|View full text |Cite
|
Sign up to set email alerts
|

Communication strategies of English native speaker teacher in the teaching and learning process in a kindergarten

Abstract: Abstract. In Dyatmika Kindergarten, the students came from different cultural backgrounds and nations. They were taught by English native speaker teacher in English sessions. The students sometimes might understand the intention of the teacher; however, sometimes they might not understand at all. Therefore, the teacher should know how they communicate with the students to avoid misunderstanding. This study aimed at identifying, describing and explaining communication strategies used by English native speaker t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
3
2
1
Order By: Relevance
“…Fillers are the only strategy in indirect strategy. This is clearly different from Mestriani et al (2018) study that they found four direct strategies (code-switching, self-repair, other-repair, self-rephrasing), three indirect strategies (use of fillers, self-repetition, other repetition), and six interactional strategies (asking for repetition, asking for clarification, asking for confirmation, guessing, comprehension check, responses). It is interesting to note that this research posits two strategies i.e.…”
Section: Teachers Communication Strategies In Synchronous Learning Co...contrasting
confidence: 96%
“…Fillers are the only strategy in indirect strategy. This is clearly different from Mestriani et al (2018) study that they found four direct strategies (code-switching, self-repair, other-repair, self-rephrasing), three indirect strategies (use of fillers, self-repetition, other repetition), and six interactional strategies (asking for repetition, asking for clarification, asking for confirmation, guessing, comprehension check, responses). It is interesting to note that this research posits two strategies i.e.…”
Section: Teachers Communication Strategies In Synchronous Learning Co...contrasting
confidence: 96%
“…The result of the study shows that thirteen communication strategies were used by the English native speaking teaching for the students teaching and learning process. Mestriani, Seken, & Putra (2018) study are in line with the study done by Pamolango (2015) about using multiple communication strategies by English native speaking teacher during English sessions at a foreign country. Pamolango (2015) also mentioned that by using filler when communicating with none English native speaker, it is really helpful.…”
Section: Literature Reviewsupporting
confidence: 89%
“…Without the fillers, the teaching process would be awkward and too formal. Mestriani, Seken, & Putra (2018) are also in line with the study by Nothash & Karafkan (2015) whereby one may content that foreign language classroom discourse is a rich source for exploring the nature, and purposes of interaction. Even more interesting it can be the teacher-employed strategies that serve different communicative purposes.…”
Section: Literature Reviewsupporting
confidence: 82%
See 2 more Smart Citations